2020
DOI: 10.7554/elife.56429
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative dissection of transcription in development yields evidence for transcription-factor-driven chromatin accessibility

Abstract: Thermodynamic models of gene regulation can predict transcriptional regulation in bacteria, but in eukaryotes chromatin accessibility and energy expenditure may call for a different framework. Here we systematically tested the predictive power of models of DNA accessibility based on the Monod-Wyman-Changeux (MWC) model of allostery, which posits that chromatin fluctuates between accessible and inaccessible states. We dissected the regulatory dynamics of hunchback by the activator Bicoid and the pioneer-like tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 127 publications
(290 reference statements)
4
68
1
Order By: Relevance
“…While we chose the initial rate of transcription as the experimental measurable to confront against our model predictions, the MS2 technique can also report on other dynamical features of transcription such as the time window over which transcription occurs and the fraction of loci that engage in transcription at any point over the nuclear cycle. While these two quantities have been shown to be relevant in shaping gene expression patterns in other regulatory contexts [Garcia et al, 2013, Lammers et al, 2020, Eck et al, 2020, Dufourt et al, 2018, Reimer et al, 2021, we found that the transcription time window was not significantly regulated in the presence of Runt. As described in Section S8, we did find some modulation of the fraction of transcriptionally engaged loci for a subset of our synthetic enhancer constructs but, as we could not detect a clear trend in how this fraction of active loci was modulated, we did not pursue a theoretical dissection of the control of this quantity by Runt.…”
Section: Measuring Transcriptional Input-output To Test Model Predictionscontrasting
confidence: 64%
See 3 more Smart Citations
“…While we chose the initial rate of transcription as the experimental measurable to confront against our model predictions, the MS2 technique can also report on other dynamical features of transcription such as the time window over which transcription occurs and the fraction of loci that engage in transcription at any point over the nuclear cycle. While these two quantities have been shown to be relevant in shaping gene expression patterns in other regulatory contexts [Garcia et al, 2013, Lammers et al, 2020, Eck et al, 2020, Dufourt et al, 2018, Reimer et al, 2021, we found that the transcription time window was not significantly regulated in the presence of Runt. As described in Section S8, we did find some modulation of the fraction of transcriptionally engaged loci for a subset of our synthetic enhancer constructs but, as we could not detect a clear trend in how this fraction of active loci was modulated, we did not pursue a theoretical dissection of the control of this quantity by Runt.…”
Section: Measuring Transcriptional Input-output To Test Model Predictionscontrasting
confidence: 64%
“…Doing so with high temporal resolution using FISH is challenging, although it can be accomplished to some degree by synchronizing embryo deposition before fixation [Park et al, 2019]. Second, while most transcription factors directly dictate the rate of RNAP loading, and hence the rate of mRNA production [Spitz and Furlong, 2012, Garcia et al, 2013, Eck et al, 2020, typical FISH measurements report on the accumulated mRNA in the cytoplasm, which is a convolution of all processes of the transcription cycle-initiation, elongation, and termination [Liu et al, 2021, Alberts, 2015]-as well as mRNA nuclear export dynamics, diffusion, and degradation. These processes could be modulated in space and time, potentially confounding measurements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We parameterize this R(t) as the sum of a constant term hRi that represents the mean, or time-averaged, rate of initiation, and a small temporal fluctuation term given by δR(t) such that R(t) = hRi + δR(t). This mean-field parameterization is motivated by the fact that many genes are well approximated by constant rates of initiation [25,31,35,61]. The fluctuation term δR(t) allows for slight time-dependent deviations from the mean initiation rate.…”
Section: Resultsmentioning
confidence: 99%